On the impact of industrial placements in professional master education: an empirical study - Wang, Lei; Xu, Liming; Guo, Yuyao; Zhang, Zelin; Xia, Xuhui; Wang, Zhaohui; Xiang, Feng (Frontiers in Education, 2025)
IntroductionDespite the rapid expansion of China's Professional Master of Engineering (PME) programs, empirical research specifically investigating industrial placements within this context remains scarce. This study aims to address this significant gap in the literature.MethodsA mixed-methods approach was employed, focusing on Mechanical Engineering PME students. Data were collected through surveys from 133 participants and analyzed using descriptive statistics and thematic analysis.ResultsAnalyses revealed moderate to high levels of satisfaction. Communication and time management were identified as key skill gains. Students expressed strong demand for expanded internship opportunities, clearer university support, and stronger company commitment regarding mentorship, compensation, and working conditions. Hypothesis testing showed no significant differences in satisfaction across gender, year of study, program type, or career plans (all p > 0.05), though interpretation is cautioned due to limited statistical power from unbalanced sample sizes.DiscussionThese findings provide new insights into the understudied context of PME industrial placements in China and highlight practical directions for enhancing university-industry collaboration. The absence of demographic differences contrasts with international evidence and suggests preliminary signs of equitable benefits. Further research with larger, multi-institutional, and longitudinal samples is needed to validate and extend these conclusions.